2020
DOI: 10.5469/neuroint.2020.00150
|View full text |Cite
|
Sign up to set email alerts
|

Canine Model for Selective and Superselective Cerebral Intra-Arterial Therapy Testing

Abstract: Purpose: With advancing endovascular technology and increasing interest in minimally invasive intra-arterial therapies such as stem cell and chemotherapy for cerebral disease, the establishment of a translational model with cerebral circulation accessible to microcatheters is needed. We report our experience catheterizing canine cerebral circulation with microcatheters, present high-resolution angiographic images of the canine vascular anatomy, describe arterial branch flow patterns and provide measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The IA route was shown to be safe and cell targeting efficiency was superior compared to the IV route in animal models 8 . Cannulation of MCA via ICA in dogs was successful using 1.2 F microcatheter in contrast to Camstra et al 28 who reported frequent vasospasms while transitioning through tortuosities of ICA. We have demonstrated an excellent safety profile for the GRP delivery procedure in all transplanted animals.…”
Section: Discussionmentioning
confidence: 59%
“…The IA route was shown to be safe and cell targeting efficiency was superior compared to the IV route in animal models 8 . Cannulation of MCA via ICA in dogs was successful using 1.2 F microcatheter in contrast to Camstra et al 28 who reported frequent vasospasms while transitioning through tortuosities of ICA. We have demonstrated an excellent safety profile for the GRP delivery procedure in all transplanted animals.…”
Section: Discussionmentioning
confidence: 59%
“…The IA route was shown to be safe and cell targeting e ciency was superior compared to the IV route in animal models 17 . Cannulation of MCA via ICA in dogs was successful using 1.2 F microcatheter in contrast to Camstra et al 18 who reported frequent vasospasms while transitioning through tortuosities of ICA. We have demonstrated an excellent safety pro le for the GRP delivery procedure in all transplanted animals.…”
Section: Discussionmentioning
confidence: 59%
“…While dogs can potentially increase drug development speeds by bypassing the phases of testing needed for a human trial, recruitment of client dogs with naturally occurring brain tumors is slow and limited by similar issues as a human trial. Moreover, in preliminary studies with non-tumor bearing canines, although ESIA infusion can be safely performed,11 the canine model presents significant limitations imposed by internal carotid artery tortuosity, high cost, and ethical handling issues 12. To address these issues, we and others13 turned to rabbits with relatively straight internal carotid anatomy, and whose costs and handling are more conducive to large studies.…”
mentioning
confidence: 99%